POLICE MISCONDUCT AND DELICTUAL LIABILITY: A DISCUSSION ON DEVELOPING VICARIOUS LIABILITY JURISPRDUENCE THROUGH A FOCUS ON THE K AND F CASES (The Pretoria Student Law Review, 2021)
Despite progress made by South African courts with respect to the ‘sufficiently close connection’ requirement to establish vicarious liability, most notably in the judgment of the Constitutional Court (CC) in K v Minister of Safety and Security, the question remains whether our judges have accepted this ground-breaking precedent and apply it in the spirit it was intended. In focusing on the minority dissenting judgment in F v Minister of Safety and Security (F) written by Yacoob J (with Jafta J concurring), I address wider issues that exist with respect to the sufficiently close connection requirement of vicarious liability as established by K. As part of this discussion, I also proceed to: (1) set out the material facts of F; (2) give an overview of the current law applicable to vicarious liability and show where F fits into that framework; (3) briefly discuss all the judgments of the Constitutional Court with respect to the framework of vicarious liability as provided; and (4) offer a critique of the minority dissenting judgment with the aim of making more general comments about the sufficiently close connection requirement in the case of (standby duty) policemen.
Keywords: vicarious liability; ‘sufficiently close connection’; K v Minister of Safety and Security; Constitutional Court (CC); F v Minister of Safety and Security; minority dissenting judgment; critique